Peace, equanimity and acceptance in the cancer experience: validation of the German version (PEACE-G) and associations with mental health, health-related quality of life and psychological constructs - Sauer, Christina; Hansen, Till; Prigerson, Holly G.; Mack, Jennifer W.; Bugaj, Till Johannes; Weißflog, Gregor (BMC Psychology, 2024)
Systematic reviews and meta-analyses reveal the importance of an accepting attitude towards cancer for mental health and functional coping. The aim of this study was to examine the psychometric properties of the German translation of the Peace, Equanimity, and Acceptance in the Cancer Experience (PEACE) questionnaire (Mack et al., 2008) and to investigate its associations with mental health, health-related quality of life (HRQoL) and related constructs.
Online veröffentlicht: 27. September 2024
Gesehen am 26.03.2025